Analytical study of wall factor on the ceiling temperature distribution in the far field for tunnel fires. Issue 171 (December 2017) - Wei, Tao; Zhao, Weifeng; Zong, Ruowen
Abstract: Based on theoretical analysis and reasonable simplification, the temperature and velocity decay along a tunnel ceiling have been deduced within a one-dimensional flow region. Comparison results show that the decays of the temperature and velocity obtained through the analytical solution are similar to those obtained using numerical methods, and agree well with the exponential distribution. In addition, the analysis results show that the decay factor of the temperature distribution along the tunnel ceiling is composed of three factors with an explicit physical significance, including the wall factor first proposed in the present study. Herein, the effects of thermally thick and thin walls are discussed. Finally, a reduced-scale experiment setup (0.5 m × 0.5 m × 5 m) established to verify the proposed model is described. The experiment results are found to agree well with the model prediction, which also proves that the wall factor has an obvious influence on the decay factor of the temperature distribution along a tunnel ceiling. Highlights: The ratio of height to width was introduced to analyze the ceiling-jet flow. Velocity decay along the tunnel ceiling have be deduced. The decay factor of temperature distribution was composed of three factors. The effect of wall factor has been analyzed.